Empowering Culinary Businesses for Economic Improvement of GKI Pamulang Church Congregation - Prasasti Perangin Angin; Gidion Putra Adirinekso; Elita Jessamine Chandra (Journal of Innovation and Community Engagement, 2025)
GKI Pamulang, located in South Tangerang, Banten, formed a community of culinary entrepreneurs to help improve the economy of the congregation. Not only due to the pandemic, most of their congregations resorted to starting a culinary business due to the huge market opportunity and the ease of starting it. However, limited experience, knowledge, and low ecosystem support make community businesses stagnant. Through the identification of problems, it was found that business management, marketing and innovation strategies, and methods of increasing business income were not yet developed well by the community members. The structured mentoring method was carried out through assessment stages, early-stage presentations, early-stage interventions, advanced-stage presentations, and follow-up interventions. Through this stages, it was found that participants showed increased understanding and changes in knowledge, including market segmentation, customer persona, value proposition, marketing methods, and market expansion to increase revenue. The causality analysis method (cause-and-effect) was used to look at pre- and post-intervention changes using 6 themes of Bill Aulet’s disciplined entrepreneurship indicators. It can be concluded that there has been a change in understanding, insight, and skills in business management, and the goals of the culinary business community for the economic improvement of the GKI Pamulang congregation can be achieved.